“Fox-like. One eye open, one eye closed”: child supervision among Syrian refugee mothers in Canada - Klassen, Christina L.; Gonzalez, Emilia; Rousseau, Cécile; Hanley, Jill; Papazian-Zohrabian, Garine; Ruiz-Casares, Mónica (Frontiers in Psychology, 2025)
When children live through violent conflict and forced displacement, the associated disruptions in their environment can profoundly affect their wellbeing and development, undermining stability and family cohesion essential for healthy growth. Adequate child supervision is an important component of supportive parenting but is understudied in the refugee migration context. Guided by the United Nations Convention on the Rights of the Child (CRC) (1989), which emphasizes the protection, provision, and participation of children as rights-holders, this study explored how Syrian refugee mothers resettled in Canada between late 2015 and 2017 perceived and practiced child supervision. Using a cross-sectional, qualitative design, we conducted semi-structured interviews with 20 mothers (half government-assisted refugees and half privately sponsored refugees) to examine their parenting across four migration stages: pre-conflict Syria, pre-flight conflict Syria, transit in various countries, and resettlement in Canada. Participants came from diverse religious and cultural backgrounds and spent varying times in transit (between 2 months to 5 years). Mothers’ narratives revealed how their approaches to children’s provision, protection, and participation evolved, shaped by material resources, social networks, and risks at each stage. Grounded in a critical children’s rights framework, the analysis of mothers’ daily negotiations highlights the dynamic and context-dependent nature of children’s rights, and the interconnections and tensions between provision, protection, and participation in child supervision. This study contributes to a deeper understanding of how refugee mothers navigate and uphold children’s rights throughout migration trajectories, advocating for policies and interventions that recognize these dynamic processes and the critical role of caregivers in ensuring children’s dignity and wellbeing.